The last chance Christmas ball - Putney, Mary Jo.; Beverley, Jo.; Bourne, Joanna; Rice, Patricia, 1949-; Cornick, Nicola; Elliott, Cara, 1951-; Gracie, Anne.; King, Susan, 1951- (New York, NY : Kensingon Publishing Corp., 2016)
"Christmas 1815. Upstairs and downstairs, Holbourne Abbey is abuzz with preparations for a grand ball to celebrate the year's most festive--and romantic--holiday. For at the top of each guest's wish list is a last chance to find true love before the New Year"--Page 4 of cover.
Prologue / Jo Beverley -- My true love hath my heart / Joanna Bourne -- A Scottish carol / Susan King -- Christmas larks / Patricia Rice -- In the bleak midwinter / Mary Jo Putney -- Old flames dance / Cara Elliott -- A season for marriage / Nicola Cornick -- Miss Finch and the angel / Jo Beverley -- Mistletoe kisses / Anne Gracie.
Keywords: Man-woman relationships -- Fiction; Christmas stories; Romance fiction; Love stories; Historical fiction